Direct Reporting of Private Sector Cross-Border Financial Flows and Stocks in Selected African Countries - Quin, Simon; Egesa, Kenneth; Murad, Howard (Washington, D.C. : International Monetary Fund, 2014)
Private cross-border financial flows and stocks have grown to account for an increasingly significant part of overall transactions and positions in many African countries. Direct reporting through enterprise surveys has become a key data source to enable them to be measured accurately. The paper describes a multi-year technical assistance project in The Gambia, Ghana, Kenya, Mauritius, Mozambique, and Nigeria, where annual enterprise surveys are now established. To varying degrees, the survey results have been incorporated into the balance of payments and International Investment Position statistics. The case studies may serve as a useful reference for other countries embarking on efforts to establish direct reporting of cross-border financial flows and stocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet